EFFECTIVENESS OF SOME NITROGEN DOSE AND CELLULOLYTIC MICROORGANISM (MOS) TOWARD DECOMPOSITION RATE OF TAN AND EMPTY AEROBIC PALM - Sakiah Sakiah; Mariani Sembiring (Agrotech Journal, 2016)
This study aims to determine the effect of nitrogen levels, cellulolytic microorganisms and the interaction of both the aerobic decomposition rate of oil palm empty fruit bunches. The research was conducted at Home Compost STIP-AP Medan in April until July 2016. Research used a factorial randomized block design consisting of two factors and three replications. The first factor is the dose of nitrogen consisting of four levels i.e. N0 = without urea, N1 = dose of Nitrogen 2% of the dry weight of TKS which is 40% as much as 48 grams, N2 = dose of Nitrogen 4% of the dry weight of TKS which is 40% as much as 96 grams, N3 = Nitrogen dose of 6% of the dry weight of TKS which is 40% as much as 144 grams. The second factor is the cellulolytic microorganism isolates comprising four levels i.e. M0 = without cellulolytic microorganisms isolates, with isolates MOS M1 = 10 ml, M2 = isolate MOS 20 ml, isolate MOS M3 = 30 ml. From the research the effectiveness of multiple doses of nitrogen and cellulolytic microorganisms (MOS) on the rate of decomposition of oil palm empty fruit bunches can be deduced as follows, namely addition of nitrogen dose was able to reduce levels of C/N was 76.4% of the levels of C/N beginning. The best treatment is contained in N3 treatment. Addition of Microorganisms treatment cellulolytic (MOS) is able to reduce levels of C/N as much as 74.6% of the levels of C/N beginning. The best treatment is contained in M3 treatment. Interaction between giving treatment cellulolytic microorganisms Nitrogen and reducing levels of C/N as much as 79.4%. Interaction best treatment there in treatment N3M3.